Pearl Millet Cover Crop Extract Inhibits the Development of the Weed Ipomoea grandifolia by Inducing Oxidative Stress in Primary Roots and Affecting Photosynthesis Efficiency - Gislaine Cristiane Mantovanelli; Adriano Antônio Silva; Letycia Lopes Ricardo; Fernanda Lima Kagami; Jéssica Dario de Almeida; Mauro Cezar Barbosa; Márcio Shigueaki Mito; Isabela de Carvalho Contesoto; Paulo Vinicius Moreira da Costa Menezes; Gabriel Felipe Stulp; Beatriz Pereira Moreno; Francielli Alana Pereira Valeze; et al. (Plants)
The cover crop Pennisetum glaucum (L.) R.Br. (pearl millet) reduces the emergence of weed species in the field through a mechanism that is not fully known. The identification of the allelopathic activity of pearl millet can contribute to the development of no-tillage techniques to produce crops without or with low doses of herbicides. This issue was investigated by testing the effects of extracts from the aerial parts of pearl millet on the germination and growth of the weeds Bidens pilosa L., Euphorbia heterophylla L., and Ipomoea grandifolia (Dammer) O’Donell under laboratory conditions. The ethyl acetate fraction (EAF) at a concentration of 2000 µg mL−1 was inactive on Bidens pilosa; it inhibited root length (−72%) and seedling fresh weight (−41%) of E. heterophylla, and in I. grandifolia the length of primary root and aerial parts and the fresh and dry weight of seedlings were reduced by 63%, 32%, 25%, and 12%, respectively. In roots of I. grandifolia seedlings, at the initial development stage, EAF induced oxidative stress and increased electrolyte leakage. At the juvenile vegetative stage, a lower concentration of EAF (250 µg mL−1) induced a stimulus in seedling growth (+60% in root length and +23% in aerial parts length) that was associated with increased photosynthetic efficiency. However, at higher concentrations (1000 µg mL−1), it induced the opposite effects, inhibiting the growth of root (−41%) and aerial parts (−25%), with reduced superoxide dismutase activity and photosynthetic efficiency. The stilbenoid pallidol was identified as the main compound in EAF. The allelopathic activity of pearl millet may be attributed, at least in part, to the impairment of energy metabolism and the induction of oxidative stress in weed seedlings, with pallidol possibly involved in this action. Such findings demonstrated that the application of the EAF extract from pearl millet can be a natural and renewable alternative tool for weed control.